PREVALENCE AND MANAGEMENT OF IRON DEFICIENCY ANEMIA IN CHILDREN: A SYSTEMATIC REVIEW - Poespo Koesoemo Aji, Raden Panji Joy; Fabiola , Kitty; Andreuy Poespo Koesoemoadi, Raden Panji; Suhartatik (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Even in affluent nations, IDA is still a significant public health issue, particularly for young children and women who are ready to have children. Aims: This systematic review is to review the treatment and prevalence of iron deficiency anemia in children. Methods: This study demonstrated compliance with all requirements by means of a comparison with the standards established by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020. Thus, the specialists were able to guarantee that the research was as current as feasible. Publications released between 2014 and 2024 were considered for this search strategy. This was accomplished by utilizing a number of distinct online reference sites, including Pubmed, ScienceDirect, and SagePub. It was determined that reviews, previously published works, and partially completed works would not be included. Result: In the PubMed database, the results of our search brought up 353 articles, whereas the results of our search on SCIENCE DIRECT brought up 8.865 articles, our search on SAGEPUB brought up 3.269 articles. The results of the search conducted for the last year of 2014 yielded a total 184 articles for PubMed, 4.071 articles for SCIENCE DIRECT and 1.144 articles for SAGEPUB. In the end, we compiled a total of 5 papers, 3 of which came from PubMed, 1 of which came from SCIENCE DIRECT and 1 of which came from SAGEPUB. We included five research that met the criteria. Conclusion: In summary, with its haematological repercussions of anemia, IDA is a prevalent and significant children health concern. To assess the effects of IDA on immunity and neurocognition, additional research is necessary. The key to successfully treating children with IDA is early identification and diagnosis of the condition together with competent interpretation of laboratory tests.